A A STUDY ON PRODUCT CUSTOMIZATION - Bassi, Willian Di Gaetano; Picchi, Marcelo Rodolfo; Gasparotto, Angelita Moutin Segoria (Revista Interface Tecnológica, 2020)
This article aims to analyze how product customization can be beneficial to business organizations, given the change in consumer market behavior. The research method adopted for the development of the article was the case study and bibliographic review. The results obtained show that the business organizations that have customized production in order to meet the specific needs of the customer may get competitive advantages, such as increased degree of customer satisfaction in addition to the increase profitability and growth of the company. It could be concluded that the company studied has in its strategic planning since its foundation the business model focused on the production of customized products.